Less is More: Concatenating Videos for Sign Language Translation from a Small Set of Signs - Silva, David Vinicius da; Estevam, Valter; Menotti, David (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI), 2024)
The limited amount of labeled data for training the Brazilian Sign Language (Libras) to Portuguese Translation models is a challenging problem due to video collection and annotation costs. This paper proposes generating sign language content by concatenating short clips containing isolated signals for training Sign Language Translation models. We employ the V-LIBRASIL dataset, composed of 4,089 sign videos for 1,364 signs, interpreted by at least three persons, to create hundreds of thousands of sentences with their respective Libras translation, and then, to feed the model. More specifically, we propose several experiments varying the vocabulary size and sentence structure, generating datasets with approximately 170K, 300K, and 500K videos. Our results achieve meaningful scores of 9.2 % and 26.2% for BLEU-4 and METEOR, respectively. Our technique enables the creation or extension of existing datasets at a much lower cost than the collection and annotation of thousands of sentences providing clear directions for future works.